1999
DOI: 10.1002/(sici)1099-1379(199901)20:1<75::aid-job872>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Organizational behavior implications of the congruence between preferred polychronicity and experienced work-unit polychronicity

Abstract: SummaryThis research hypothesizes that greater congruence between preferred polychronicity (the extent to which an individual prefers to be involved with several tasks simultaneously) and experienced work-unit polychronicity (the polychronic behaviors and preferences of the supervisor and co-workers) will be associated with higher levels of (1) three components of organizational commitment (willingness to exert eort, desire to remain a member of the organization, and belief in and acceptance of organizational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
133
2
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(150 citation statements)
references
References 43 publications
6
133
2
1
Order By: Relevance
“…First, Slocombe and Bluedorn (1999) examined the fit individual-and team-level polychronicity. Using polynomial regression analysis and response surface methodology (see Edwards, 2002), Slocombe and Bluedorn found that the fit between the polychronicity of team members was significantly related to self-reported performance (as well as organizational commitment).…”
Section: Polychronicity and Performancementioning
confidence: 99%
See 1 more Smart Citation
“…First, Slocombe and Bluedorn (1999) examined the fit individual-and team-level polychronicity. Using polynomial regression analysis and response surface methodology (see Edwards, 2002), Slocombe and Bluedorn found that the fit between the polychronicity of team members was significantly related to self-reported performance (as well as organizational commitment).…”
Section: Polychronicity and Performancementioning
confidence: 99%
“…The person-environment and person-job fit perspectives offer a useful avenue for designing such research, and there is already some first evidence supporting it Slocombe & Bluedorn, 1999), although more work is needed.…”
Section: Polychronicity and Performancementioning
confidence: 99%
“…Polychronicity is defined as an individual's preference for performing multiple tasks at once (Slocombe & Bluedorn, 1999). Individuals higher in polychronicity are therefore more likely to prefer and engage in multitasking activities.…”
Section: Polychronicitymentioning
confidence: 99%
“…First, temporal issues span the individual-to-workgrou p level, where changes to the temporal structure of work are most prominent. Here, perceptions of time tend to become increasingly polychronic (vs. monochronic) (see Bluedorn, Kauffman, & Lane, 1992;Slocombe & Bluedorn, 1999). In the context of work, polychronicity means that tasks are less sequentially ordered and more frequently done in parallel.…”
Section: A Temporal Perspectivementioning
confidence: 97%